Resting heart rate and anaerobic power output variability in cyclists after single-joint versus multi-joint intervention exercises - Mendoza, Andrei Franco Z. 1999-
Cycling as a sport requires high intensity endurance based training focusing on aerobic capacity. In this study, the researcher incorporated anaerobic resistance training mainly, focusing on leg exercises adapted from an existing protocol (Gentil and Bottaro, 2010) from a single-joint and multi-joint intervention exercises to determine if there will be significant effect on resting heart rate (RHR) and power output (PO) variability among recreational cyclists. The study included 10 recreational cyclists divided into 2 groups (MJ = 5 ; SJ = 5). They were tested for initial RHR. Weight (kg), and power output on a Monark Cycle Ergometer following a 10 -second modified Wingate Anaerobic Test (WAT). The exercise intervention was carried out in a four-week timeline. Each group performed a general warm up before the actual exercise. Proper loading was implemented by the researcher based on NSCA guidelines.